Rankings and risk-taking in the finance industry - Michael Kirchler; Florian Lindner; Utz Weitzel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
Rankings are a pervasive feature of the finance industry. Although they have no direct monetary consequences, rankings provide utility for intrinsic (positive self-image) and extrinsic (status) reasons. We recruit a unique subject pool of 204 financial professionals and investigate how anonymous rankings influence risk-taking in investment decisions. We find that rankings increase risk-taking because of financial professionals' desire for positive self-image. This particularly applies to underperformers, who take the highest risks. Incentivizing rankings monetarily does not further increase risk-taking. In a comparative study with 432 students we find that student behavior is not driven by rankings.
Keywords: G02; G11; D03; C93; 330; experimental finance; behavioral finance; rank incentives; rankings; financial professionals; investment game; framed field experiment; tournament incentives